Analytical Science - Chapter 3 - Woodget, Brian (The University of Hull)
Most samples require some form of sample pre-treatment/preparation, before analysis can be attempted. The sample preparation may involve either physical or chemical transformation of the analyte species and/or concentration/separation. This chapter compares the various of ways that these processes may be carried out and finally looks in more detail at the technique of solvent extraction.